Macroeconomic Determinants of Foreign Direct Investment in Indonesia: The Role of GDP, Inflation, and Exchange Rate (1990–2023) - Dari, Tri Ulan; Astuti, Rini Dwi (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2025)
This study explores the influence of key macroeconomic indicators—Gross Domestic Product (GDP), inflation, and exchange rate—on Foreign Direct Investment (FDI) inflows in Indonesia from 1990 to 2023. Using the Error Correction Model (ECM), the research analyzes both long-term and short-term dynamics to offer a more comprehensive understanding of the relationship between these variables and FDI performance. The results show that GDP has a significant positive effect on FDI in both time horizons, reinforcing the notion that economic growth enhances investor confidence and market potential. In contrast, inflation does not exhibit a significant effect on FDI, suggesting that investors may perceive inflation in Indonesia as relatively stable and manageable. The exchange rate demonstrates a dual effect: it negatively affects FDI in the long term, indicating that prolonged currency depreciation deters investment, while in the short term, it positively influences FDI, as a weaker rupiah may reduce investment costs. Diagnostic tests confirm the reliability and validity of the regression model, including the absence of multicollinearity, heteroskedasticity, and autocorrelation. The study concludes that GDP and exchange rate stability are crucial for attracting and sustaining foreign investment, while inflation remains a less decisive factor in the Indonesian context. These findings offer practical implications for policymakers to prioritize macroeconomic stability and growth-oriented strategies to enhance Indonesia’s competitiveness as an FDI destination.